Enzymatic hydrolysis of proteins from snakehead-fish (Channa striata). Issue 1 (July 2020) - Hariyati, H; Mahendradatta, M; Tawali, A B; Langkong, J
Abstract: The purpose of this research is to study the characteristics and bioactive components of the production of snakehead fish ( Channa striata ) protein hydrolysates through enzymatic methods. The enzymes used in this study were the papain enzyme and without the enzyme as a comparison. Substrate used is fresh snakehead fish ( Channa striata ) obtained from fish reservoirs. Analysis carried out in the form of total degrees of hydrolysis and nitrogen content in protein. The results showed that the use of the papain enzyme was excellent in producing snakehead fish ( Channa striata ) protein hydrolyzate. The papain enzyme helps break down fish protein into peptides or amino acids.